Hak Digital Lansia sebagai Pelaku Begging Digital di Live Video TikTok - Fatohu Jonathan Marunduri; Ai Permanasari (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The act of Digital begging or online begging carried out by elderly people in live videos on the TikTok platform has sparked controversy, raising the question of whether the elderly have digital rights that must be protected, as such activities have the potential to cause negative impacts. This study aims to answer two main questions: (1) how can the digital rights of the elderly be understood in the context of their role as perpetrators of digital begging on TikTok, (2) what is TikTok's responsibility in providing digital rights to the elderly as perpetrators of digital begging on TikTok live videos, and (3) how can the law provide protection for the digital rights of the elderly Using a normative juridical approach, this study examines relevant legal rules and norms such as Law Number 14 of 1998 concerning the Welfare of the Elderly, Law -Law Number 39 of 1999 concerning Human Rights, as well as international regulations such as the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights (ICCPR), and draws on best practices from other countries. The results of the study show that the elderly are permanent legal subjects who have digital rights, including as perpetrators of digital begging on live TikTok videos, and in this case, Indonesia has a legal vacuum regarding the digital rights of the elderly. Therefore, regulatory updates are needed that explicitly regulate the digital rights of the elderly, either through the revision of Law Number 14 of 1998 concerning Elderly Welfare or integration into Law - Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 27 of 2022 concerning Personal Data Protection.